PERAN KOPERASI DALAM MENDUKUNG PENGEMBANGAN DAN PENGUATAN UMKM: STUDI KASUS DI KOPERASI NEW MITRA KARYA MEDAN - Umayya Gea, Wardatul; Nikira, Nikira; Khairulnisa, Khairulnisa; Hayati, Fitri (LP2M Universitas Bina Bangsa, 2025)
Cooperatives have a strategic role in supporting the development and strengthening of Micro, Small, and Medium Enterprises (MSMEs), especially in the aspects of capital, training, and market access. This study aims to analyze the role of the New Mitra Karya Medan Cooperative in supporting the strengthening of MSMEs through a qualitative approach with a case study method. The results show that cooperatives play a significant role in providing access to low-interest capital, facilitating entrepreneurship training, and expanding market access through local cooperation. However, challenges such as limited cooperative capital, low member participation, and lack of innovation in digitalization still need to be overcome. The role of cooperatives can be carried out through increasing funding, organizing training based on the needs of MSMEs, and applying digital technology in marketing. This research has implications that cooperatives can be strategic partners in empowering MSMEs to increase competitiveness and contribute to sustainable local economic growth.